Impact of sudden stratospheric warmings on the stratosphere-to-troposphere transport of ozone - Lee, Jaewon; Butler, Amy H.; Albers, John R.; Wu, Yutian; Lee, Simon H. (Geophysical Research Letters, 2025)
Funding: J. L. and Y. W. are supported by the U.S. National Science Foundation award AGS‐1802248. Sudden stratospheric warmings (SSWs) can significantly impact tropospheric weather systems. Previous studies suggest that SSWs may also influence stratosphere-to-troposphere transport (STT), but their spatial and temporal distribution and mechanisms are not fully understood. The complex relationships between SSWs and the El Niño-Southern Oscillation (ENSO) have also made it difficult to isolate the effects of SSWs on STT. From an idealized ENSO simulation with the WACCM4 model using a stratospheric origin ozone tracer, we investigate the effect of SSWs on the STT of ozone under different ENSO phases. We find a significant increase in lower tropospheric ozone from the SSW onset up to 3 months later over the Arctic, North America, and Europe, regardless of the ENSO phase. This study highlights the significant influence of SSWs on STT on a subseasonal scale. Our results also emphasize the need to consider SSWs when addressing the ENSO impact on STT. Peer reviewed